Effect of microbial community on the formation of flavor components in cigar tobacco leaves during air-curing - Lin Zhang; Wenlong Li; Zheng Peng; Juan Zhang (BMC Microbiology)
Abstract Background The air-curing process of cigar tobacco leaves is typically conducted in an open environment, involving the participation of various microorganisms. However, the effect of microbial communities during air-curing process on the formation of flavor components remains unclear. Therefore, this study aims to reveal the dynamics of flavor components and microbial community changes, and explore the potential role of microbial communities in flavor formation during the cigar tobacco air-curing process. Results High-throughput sequencing analysis showed that Pantoea, Sphingomonas and Pseudomonas were the dominant bacterial genera during air-curing process, while Aspergillus was the dominant fungal genus. Subsequently, volatile flavor analysis shows that alkaloids were the most important volatile compounds in cigar leaves, followed by esters, alcohols and aldehydes. Furthermore, 38 characteristic volatile flavor compounds at different periods of air-curing were identified based on PLS-DA in different periods of air-curing. The correlation analysis between microorganisms and flavor components showed that Pantoea and Staphylococcus might promote the flavor formation from browning to post-air-curing and were positively correlated with specific flavor components like phenylacetaldehyde and acetophenone. Phoma, Mycosphaerella, Wallemia, and Cladosporium were identified as key fungal genera influencing flavor formation, as they showed positive correlations with multiple flavor components. These information enrich our understanding of the flavor formation of cigar tobacco during air curing. Conclusions There is a complex correlation between the microbial community and the flavor components, which may have a great influence on the flavor formation during the air-curing process of cigar leaves. Bacterial communities have higher species diversity and richness during air-curing, and have more complex correlation characteristics with volatile flavor, which may play more roles in the flavor formation. This study revealed the potential role of microbial community on flavor formation in cigar tobacco air-curing process, and provided guidance for subsequent screening of specific functional microorganisms to improve and stabilize cigar tobacco flavor.